Extraction of Chicken Bone as Alternative Source of Calcium Incorporated in Bread - Abdul Kadir, Muhammad Asyraf; MERIAM SUHAIMY, DR SYAZWAN HANANIE BINTI MERIAM SUHAIMY; PAUZAN, MOHAMMAD ARIF BUDIMAN BIN PAUZAN; Saliza Asman; Zalilah Murni Yunus; Mohd Hanafi Mohd Hafidzal (Enhanced Knowledge in Sciences and Technology, 2024)
The composition of chicken bones comprises approximately 70% inorganic matter and 30% organic matter. The composition of the inorganic matter comprises calcium phosphate, calcium carbonate, and magnesium phosphate. Calcium is essential for numerous vital bodily processes adults have a recommended daily calcium intake (RDI) of 1,000 milligrams (mg). In this study, the calcium contain in the chicken bone will be extracted by using an alkaline treatment. Then the extracted chicken bone will be analysed for it physicochemical and mineral contain. The extracted chicken bone will be added to the bread to enhance the calcium contain in the bread. The effect of bread that has been fortified with chicken bone powder will be analysed further to determine the sensory, texture, colour and nutritional contain. This study shows the calcium content for extracted chicken bone that have been analysed using Atomic Absorption Spectroscopy was higher than normal chicken bone which is 11555.36mg/100g. Besides that the pH and moisture for extracted chicken bone was lower compared to the chicken bone powder. There are significant difference that detected in the texture of the bread with extracted chicken bone powder compared to common bread by using texture analyzer to determine the firmness and springiness of the bread. There are no significance difference for bread with extractd chicken bone powder in terms of color for L* and a* value but there are significant different with common bread for b* value. 50 panellist has been chosen to conduct for sensory analysis of bread and the panellists more preferred to the bread with extracted chicken bone powder. For the proximate analysis of bread with extracted chicken bone powder there are significant differences for moisture and ash contain compared to the common bread. Overall results shows that the extracted chicken  bone powder has an impact to the properties of bread and the yield value for the calcium content for the powder was higher. This shows that the extracted chicken bone powder can be used as a calcium source for enrichment in food.